Macau's Trade with the Portuguese Speaking World - Paul B. Spooner (Journal of Global Initiatives, 2016)
Macau has boomed over the last decade as its gaming industry has provided the massive Chinese economy with the only legal casino gambling services in the nation. But, recent Chinese political changes have resulted in a sharp downturn in Macau’s gambling revenues despite a major expansion of its gaming facilities. This may negatively impact efforts to promote a relationship between Macau and the Portuguese Speaking World. Portugal with its former Ultramar, to which Brazil has been added, is now termed “Lusophonia.” Initiated by China in Macau in October 2003, the efforts to promote a Lusophone trade and economic relationship with China through Macau have not resulted in any significant trade or tourist links between Macau and Lusophonia. Despite China’s trade with Brazil booming following China’s entry into the World Trade Organization in 2001, its Brazilian trade is routed either through China itself or Hong Kong, not through Macau. Macau’s significantly weak links to Lusophonia, which were predictable from international trade theory that included the Gravity Model and Ghemawat’s CAGE analytical model, were not enhanced during Macau’s 10 year boom from 2004 to 2014, and may be forced to take a back seat to the re-positioning of its gaming industry over the next several years.